Evaluasi Unjuk Kerja Kompresor Screw Ml45 di Unit Boiler PPSDM Migas Cepu - Michael Max Sitompul; Hafid Suharyadi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the performance of the ML45 Screw compressor based on field observation data. Based on the observation and data analysis, several conclusions can be drawn. First, the actual capacity of the compressor decreased by about 33.12% from 100% initial condition of 261.22 CFM to 66.87% of 174.7 CFM. This decrease is due to the difference in operational pressure which is lower than the design pressure. Secondly, the power generated by the current compressor is about 31.6 KW, which is lower than the design power of 45 KW. This decrease in power is due to the low input temperature. These findings indicate the importance of considering actual operational conditions in optimizing compressor performance. In this context, further adjustments or evaluations are recommended to ensure optimal performance of the ML45 Screw compressor. Factors such as operational pressure and input temperature should be carefully considered to achieve the expected results. This research provides valuable insights for the industry in understanding the factors affecting compressor performance and provides a basis for future performance improvements. These efforts are expected to improve operational efficiency and reduce potential losses in the use of Screw ML45 compressors.